2016
DOI: 10.1007/s13300-016-0222-7
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide Add-on to Continuous Subcutaneous Insulin Infusion Therapy Reduces Bolus Insulin Doses in Patients with Type 2 Diabetes: A Randomized, Controlled, Open-Label Trial

Abstract: IntroductionThe objective of this study was to investigate the effect of adding exenatide to continuous subcutaneous insulin infusion (CSII) therapy on the precise insulin doses required by type 2 diabetic patients to maintain glycemic control.MethodsThis was a single-center, randomized, controlled, open-label trial. Uncontrolled T2D patients were recruited between March 2010 and November 2011 at Nanjing First Hospital, China. Subjects were randomly assigned (1:1) to either an exenatide add-on to CSII group or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…CSII therapy was provided with aspart (Novo Nordisk, Bagsvaerd, Denmark) using a Medtronic insulin pump (Northridge, CA) as previously described [ 6 , 18 , 20 ]. After subjects achieved glycemic control, defined as a fasting and 2-h post prandial capillary blood glucose concentration between 6.1 and 8.0 mmol/l [ 21 ], patients were randomized 1:1 to two groups receiving: (1) 4 days of Novo Mix 30 (Novo Nordisk, Bagsværd, Denmark) followed by 2 days of Humalog Mix 50 (humalog ® Mix50™, Eli Lilly and Co., Indianapolis, IN, USA); (2) 4 days of Humalog Mix 50 followed by 2 days of Novo Mix 30. Initial premixed insulin doses were calculated as 0.4–0.5 IU/kg, and doses were subsequently adapted according to capillary glucose values obtained by self-monitoring during the first 2 days of the premixed insulin titration period.…”
Section: Methodsmentioning
confidence: 99%
“…CSII therapy was provided with aspart (Novo Nordisk, Bagsvaerd, Denmark) using a Medtronic insulin pump (Northridge, CA) as previously described [ 6 , 18 , 20 ]. After subjects achieved glycemic control, defined as a fasting and 2-h post prandial capillary blood glucose concentration between 6.1 and 8.0 mmol/l [ 21 ], patients were randomized 1:1 to two groups receiving: (1) 4 days of Novo Mix 30 (Novo Nordisk, Bagsværd, Denmark) followed by 2 days of Humalog Mix 50 (humalog ® Mix50™, Eli Lilly and Co., Indianapolis, IN, USA); (2) 4 days of Humalog Mix 50 followed by 2 days of Novo Mix 30. Initial premixed insulin doses were calculated as 0.4–0.5 IU/kg, and doses were subsequently adapted according to capillary glucose values obtained by self-monitoring during the first 2 days of the premixed insulin titration period.…”
Section: Methodsmentioning
confidence: 99%
“…Not only did the SD, IQR, and LAGE, which reflect the intraday glycemic variability, improve, but the MODD, which represents the day-to-day glycemic variability, decreased. A clinical study on another GLP-1 analog, exenatide [25], also demonstrated that the addition of exenatide to CSII decreased glucose variability, exhibited by a significant reduction in MAGE. Our findings are in accordance with this previous study and corroborate the finding that the addition of GLP-1 analog to CSII in poorly controlled T2DM can improve GV.…”
Section: Discussionmentioning
confidence: 95%
“…CGM data were obtained with Medtronic Minimed CGMS Gold; this was performed as previously described [ 15 ]. The data collected from the CGMS were (1) 7 a.m. day 2 to 7 a.m. day 3 and (2) 7 a.m. day 4 to 7 a.m. day 5.…”
Section: Methodsmentioning
confidence: 99%